Transformation of Islamic Religious Practices in the Digital Era: Opportunities and Challenges for Contemporary Da'wah - Khadiq; Isma Indriyani, Putri (Jurnal Dakwah, 2023)
The development of digital technology has significantly transformed various aspects of life, including the religious practices of Muslims. In this digital era, religious practices such as worship, religious learning, and the dissemination of Islamic values have undergone changes influenced by the ease of access to information and digital media platforms. This study aims to analyze the impact of digital transformation on the religious practices of Muslims, focusing on the opportunities and challenges faced in contemporary da'wah. Identified opportunities include the expanded reach of da'wah, efficiency in delivering messages, and global connectivity among Muslims. However, challenges such as the misuse of technology, biased information, and the lack of digital literacy in society also require attention. Through a qualitative approach, this study explores strategies that da'i (preachers) can adopt to maximize digital media as an effective and contextually relevant tool for da'wah in today's socio-cultural landscape.